Effect of pregnancy on pre-existing liver disease: Chronic viral hepatitis - Sookoian, Silvia Cristina (2006)
Women with viral chronic hepatitis generally do quite well during pregnancy, providing that they have not progressed to decompensated cirrhosis. As a general rule, a stable liver equals a safe pregnancy. However, concern is about how pre-existing chronic liver disease may affect the pregnancy and the unborn baby. This review plans to answer some key questions regarding this issue in order to provide to healthcare professionals updated information of the current knowledge in this field. Besides, a synopsis of the following subject matters are reviewed, for instance, the main risk factors associated with vertical transmission of HBV and HCV in pregnant women chronically infected, the influence of pregnancy on HBV and HCV viral load and the effect of pregnancy on the clinical course of chronic hepatitis. Lastly, it is included a list of recommendations to decrease vertical transmission rates of chronic viral hepatitis as well as some information for the reproduction team.